If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3y = 44 Solving 2x + -3y = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 2x + -3y + 3y = 44 + 3y Combine like terms: -3y + 3y = 0 2x + 0 = 44 + 3y 2x = 44 + 3y Divide each side by '2'. x = 22 + 1.5y Simplifying x = 22 + 1.5y
| 3x^2+2x=4-7x | | x^2+4mx+8-4m=0 | | (12x^2)= | | 4m^2=24 | | y^(1/4) | | x^2-300x-30000=0 | | -1/3(3w-15)=-1/5(25-5w) | | 20p/3=40*3 | | (2y+1)(y-3)-3y(y+2)=y(2-y)+10 | | 2n-1=5n | | 8x12/4-?=2 | | 5m+12y=7y | | 4(2x+1)=6(x+12) | | 9(2x+3)=3(5x+4) | | 5(x+1)=4x+17 | | 3(x+9)=x+13 | | 4(x+4)=3x+22 | | x^2-90x-450=0 | | 5m+12=8md | | 2x+1=x^2-2x+1 | | 2682/8 | | ax^4+bc+c=0 | | 5-n/3=1 | | 8*3m=-3+6m | | x*0.07=1760 | | -2x-(x-1)+8=0 | | 4m+3m=1880 | | 48x+7y=1 | | 48x+11y=1 | | 5d-8=11 | | b+5+5=8 | | (8x-3)^(3/2)=0 |